2013
DOI: 10.4103/0976-9668.116972
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of dental care: An Indian outlook

Abstract: Oral health has a significant impact on the quality of life, appearance, and self-esteem of the people. Preventive dental visits help in the early detection and treatment of oral diseases. Dental care utilization can be defined as the percentage of the population who access dental services over a specified period of time. There are reports that dental patients only visit the dentist when in pain and never bother to return for follow-up in most cases. To improve oral health outcomes an adequate knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 18 publications
0
57
0
1
Order By: Relevance
“…Patients are not covered under any type of insurance and generally pay out of their pockets to get treatment from both public and private dentists. 18 Strategies that target parents and not just children may also help to address oral health disparities in children as it has been reported that parental dental care behaviors have an important effect on the health behavior of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are not covered under any type of insurance and generally pay out of their pockets to get treatment from both public and private dentists. 18 Strategies that target parents and not just children may also help to address oral health disparities in children as it has been reported that parental dental care behaviors have an important effect on the health behavior of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Cost of the treatment has a recognized influence on the utilization of oral health services. 25 About 3% individuals never visited the dentist because they were afraid of the dental treatment. Various studies have shown that high levels of dental anxiety are associated with reduced or irregular dental care utilization or seeking care only in case of emergency.…”
Section: Discussionmentioning
confidence: 99%
“…India has a large number of dental schools that are distributed across the country, many of which are located in urban settings, where HIV prevalence is high. 12 The study was reviewed and approved by the Ethics Committee of the Institute (Ref.…”
Section: Methodsmentioning
confidence: 99%